Justification, Judgment, and Participation: A Reply to Michael Horton - Prothro, James B. (Pro ecclesia, 2024)
This article offers a grateful reply to Michael Horton's in this same issue regarding the doctrine of justification in the letters of Paul. In it, I express thanks and highlight agreements between his and my views of justification, and then discuss disputed aspects of the language of justification, the relationship of one's justification by faith in Christ to the final judgment according to works done in Christ, and the interrelation of justification to participation in Christ through the Spirit.